PENGGUNAAN MEDIA DALAM PEMBELAJARAN BAHASA ARAB - Nurkholis, Nurkholis (JURNAL TARBAWIYAH, 2015)
Arabic is one of foreign language and the given in schools in Indonesia. Learning a foreign language will have difficulties because the majority of these languages are very seldom or never heard before. Therefore, in the process required learning media or a good learning tool so that the learning process can well received by the students. Learning media is very diverse, from the simplest and can be created themselves up to a super-sophisticated electronic media and the media each having a different character, therefore the selection of media to be selective, because the media used must be able to support the objectives, understanding , as well as the motivation of learning. In the process of learning the Arabic language media is very desirable, because Arabic is the material that is considered to be difficult, it is necessary to appropriate learning media in its delivery. By using the media is expected to simplify and improve the motivation of the students in learning the Arabic language.